A Recourse Stochastic Goal Programming Approach for the Multi-objective Stochastic Vehicle Routing Problem - Masri, Hatem; Ben Abdelaziz, Fouad; Alaya, Houda (Journal of multi-criteria decision analysis, 2016)
This paper addresses a multi‐objective stochastic vehicle routing problem where several conflicting objectives such as the travel time, the number of vehicles in use and the probability of an accident are simultaneously minimized. We suppose that demands and travel durations are of a stochastic nature. In order to build a certainty equivalent program to the multi‐objective stochastic vehicle routing problem, we propose a solution strategy based on a recourse approach, a chance‐constrained approach and a goal‐programming approach. The resulting certainty equivalent program is solved to optimality using CPLEX. Copyright © 2016 John Wiley & Sons, Ltd.